(untitled) (Academia Journal of Medicine, 2024)
The goal of the current study was to compare the shear bond values of zirconia-reinforced glass ionomer cement and conventional glass ionomer cement. A collection of 20 extracted premolars with unbroken buccal or lingual surfaces was made. The whole sample was randomly split into two groups: Group A (n=10) which was Conventional Glass Ionomer Cement and Group B (n=10) which was Zirconia Reinforced Glass Ionomer Cement (Zirconomer). The process of thermocycling was used to mimic oral conditions.